ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI, KONSUMSI DAN IMPOR KEDELAI DI INDONESIA - Sari, Putri Meiliza; Aimon, hasdi; Syofyan, Efrizal (Jurnal Kajian Ekonomi, 2014)
This study aims to analyze (1) the effect of land area, the price of localsoybean, seed and fertilizer to soybean production in Indonesia, (2) the effect ofsoybean production, soybean import, per capita income, and consumption of soyprevious period to soybean consumption in Indonesia, (3) the effect of per capitaincome, the level of the real exchange rate and the price of imported soybean tosoybean import in Indonesia. The data source is a secondary data as well as datain the form of time series from 1983 to 2012 . Research use simultaneous equationmodel analysis in the form of Indirect Least Squares (ILS). The effect of the landarea of soybean and fertilizer have significant effect on soybean production withregression coefficients 1.26 and 0.84. Local soybean prices and soybean seed doesnot have significant impact on soybean production. Soybean production, Soybeanimport and consumption of soybean previous period have significant effect onsoybean consumption with regresion coefficients 0.72, 0.85 and 0.34, but percapita income there is no significant effect on soybean consumption. Per capitaincome and the price of imported soybean have significant effect on soybeanimport with regression coefficients 0.11 and 226.6. Value of the real exchangerate of the rupiah against the U.S. dollar there is no significant effect on soybeanimport.Keywords : Soybean Production, Soybean Consumption and Soybean Import.